Synthesis and Characteristics of Microencapsulated Myristic Acid with TiO2 as Composite Thermal Energy Storage Materials - Zhaohe WANG (Kaunas University of Technology, 2021)
To solve the issues of flowing and leaking of myristic acid (MA) as phase change energy storage material in practical application, a novel microencapsulated composite phase change energy storage material was prepared by sol-gel method using myristic acid (MA) as core material and titanium dioxide (TiO2) as shell material. The chemical structure, crystal structure, micromorphology, phase change characteristics and thermal stability of phase change microencapsulated energy storage materials were characterized by using Fourier transform infrared spectrometer (FT-IR), X-ray diffraction analyzer (XRD), field emission scanning electron microscope (FE-SEM), differential scanning calorimetry (DSC), thermogravimetric analyzer (TGA). The consequents illustrated that the ideal sample melted at 54.97 °C with the latent heat of 55.76 J/g and solidified at 49.85 °C with the latent heat of 54.55 J/g. In general, the prepared microencapsulated phase change materials possessed good thermal properties and thermal stabilities. It is predicted that the shape-stabilized MA/TiO2 composites have great potential for thermal energy storage.